(untitled) (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we give a recursive method in constructing a breadth-first search tree for multiplicative circulant graphs of order power of odd. We then use the proposed construction in reproving some results concerning multiplicative circulant graph’s diameter, average distance and distance spectral radius. We also determine the graph’s Wiener index, vertex-forwarding index, and a bound for its edge-forwarding index. Finally, we discuss some possible research works in which the proposed construction can be applied.